Overview of the biodiversity and distribution of the Class Homoscleromorpha in the Tropical Western Atlantic. In: Schönberg CHL, Fromont J, Hooper NA, Sorokin S, Zhang W, de Voogd N (eds) New Frontiers in Sponge Science – the 2013 Fremantle Sponge Conference. - Domingos, C.; Lage, A.; Muricy, G. (Journal of the Marine Biological Association of the United Kingdom, 2016)
In this study we revise the current knowledge on the biodiversity and distribution of the Class Homoscleromorpha in the Tropical Western Atlantic (TWA). Twenty-seven species are currently recognized in the TWA, belonging to the genera Oscarella (O. nathaliae), Plakortis (P. angulospiculatus, P. dariae, P. edwardsi, P. halichondrioides, P. insularis, P. microrhabdifera, P. myrae, P. petrupaulensis, P. potiguarensis, P. simplex, P. spinalis, P. zyggompha), Plakinastrella (P. globularis, P. microspiculifera, P. onkodes, P. stinapa), Plakina (P. coerulea, P. elisa, P. jamaicensis, P. monolopha, P. tetralopha, P. trilopha, P. versatilis), Corticium (C. diamantense, C. quadripartitum) and Tetralophophora (T. mesoa- mericana). Three of these ‘species’ are cosmopolitan and in fact represent complexes of cryptic species: Plakina monolopha, P. trilopha and Plakortis simplex. All other 24 species reported are TWA endemics. Only four species are found both in the Caribbean and in Brazil: Plakortis angulospiculatus, P. halichondrioides, Plakinastrella microspiculifera and P. onkodes, but these may also be species complexes. Seven species are Brazilian endemics: Plakina coerulea, Plakinastrella globularis, Plakortis insularis, P. microrhabdifera, P. petrupaulensis, P. potiguarensis and P. spinalis. Thirteen species are restricted to the Tropical North-western Atlantic: Corticium diamantense, C. quadripartitum, Oscarella nathaliae, Plakina elisa, P. jamaicensis, P. tetralopha, P. versatilis, Plakortis dariae, P. edwardsi, P. myrae, P. zyggompha, Plakinastrella stinapa and Tetralophophora mesoamericana. The Greater Antilles is the richest ecoregion, with 12 species reported. Only the Guianan ecoregion has no records of Homoscleromorpha. Several undescribed species of Oscarella and Plakina are also known from the TWA. We estimate that the biodiversity of Homoscleromorpha in the TWA is at least twice as high than currently known.
Proceedings of the 9th International Sponge Conference